Multidisciplinary approach to the study of large-format oil paintings - Calderón Mesén, Paula (2023)
Cultural heritage has become a keystone for comprehending our society, as it represents and reflects our origins, passions, beliefs and traditions. Furthermore, it provides fundamental information about specific temporary spaces, materials’ availability, technology, artist’s intention, and site weather conditions. Our aim was to develop a multidisciplinary approach with a main focus on investigating two Italian large-format paintings located in highly diverse environments such as the National Theater of Costa Rica. We monitored environmental conditions and quantified fungal aerial spores. Then, we determined regions of possible biodeterioration with the software MicroorganismPattern and used the software PigmentArrangement to elucidate the apparent colour of the paintings based on distribution and arrangement of the pigment crystals. Finally, we characterized eight genera of calcareous nannofossils found in the ground layers of the artwork. The former Men’s Canteen at the National Theater of Costa Rica presented a mean air temperature of 23.5 C, a relative humidity of 72.7% and a concentration of CO of 570 ppm. The fungal aerial concentration was 1776 spores/m . The software MicroorganismPattern identified 32 sampling regions, out of which 11 were positive for microbial contamination. The software PigmentArrangement determined that the blue crystals (ultramarine pigment) had the shortest distances between themselves (29 μ m). Finally, the nanofossils identified enabled us to restrict the age of the material to a biostratigraphic interval ranging from Coniacian to Maastricthian ages. By using a multidisciplinary approach we were able to explore the diptych, suggest a set of minimally invasive perspectives in tropical environments to be used worldwide and obtain key information about the artist’s artistic process, materials used along with better understand its state of conservation.